2007
DOI: 10.1007/s10393-006-0078-9
|View full text |Cite
|
Sign up to set email alerts
|

Dryland Salinity and Ecosystem Distress Syndrome: Human Health Implications

Abstract: Clearing of native vegetation for agriculture has left 1.047 million hectares of southwest Western Australia affected by dryland salinity, and this area may expand up to a further 1.7-3.4 million hectares if trends continue. Ecosystems in saline-affected regions display many of the classic characteristics of Ecosystem Distress Syndrome, one outcome of which has not yet been investigated in relation to dryland salinity: adverse human health implications. This article seeks to review existing information and ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 70 publications
0
43
0
Order By: Relevance
“…Some of the relevant issues presented in the literature which could be used in a cost-benefit analysis include: the economic case for government intervention and the overall cost of dryland degradation (Kirby and Blyth 1987;Beresford 2001;Roberts and Pannell 2009;Graham et al 2010), spatial modelling and identification of dryland areas affected by salinization (Graham 1992;Ive et al 1992;Horwood 1994;Kirkby 1996;Furby et al 2010), farmers and community perceptions about the salinization problem and the proposed alternatives (Greiner 1997;Hartley et al 1998;Kington et al 2003;Khan et al 2008;Kingwell et al 2008); landscape or river basin management options (Greiner 1998;Callow 2011Callow , 2012, modelling of on-farm management alternatives and economic trade-offs (John et al 2005;Cheng et al 2009;Finlayson et al 2010;Graham et al 2010), reintroduction of native trees and shrubs (Schofield 1992;Dorrough and Moxham 2005;Thrall et al 2005), and the effects of dryland degradation on human health (Jardine et al 2007(Jardine et al , 2008a(Jardine et al , 2008b(Jardine et al , 2011Speldewinde et al 2009Speldewinde et al , 2011.…”
Section: Economic Costs Of Dryland Rehabilitationmentioning
confidence: 99%
“…Some of the relevant issues presented in the literature which could be used in a cost-benefit analysis include: the economic case for government intervention and the overall cost of dryland degradation (Kirby and Blyth 1987;Beresford 2001;Roberts and Pannell 2009;Graham et al 2010), spatial modelling and identification of dryland areas affected by salinization (Graham 1992;Ive et al 1992;Horwood 1994;Kirkby 1996;Furby et al 2010), farmers and community perceptions about the salinization problem and the proposed alternatives (Greiner 1997;Hartley et al 1998;Kington et al 2003;Khan et al 2008;Kingwell et al 2008); landscape or river basin management options (Greiner 1998;Callow 2011Callow , 2012, modelling of on-farm management alternatives and economic trade-offs (John et al 2005;Cheng et al 2009;Finlayson et al 2010;Graham et al 2010), reintroduction of native trees and shrubs (Schofield 1992;Dorrough and Moxham 2005;Thrall et al 2005), and the effects of dryland degradation on human health (Jardine et al 2007(Jardine et al , 2008a(Jardine et al , 2008b(Jardine et al , 2011Speldewinde et al 2009Speldewinde et al , 2011.…”
Section: Economic Costs Of Dryland Rehabilitationmentioning
confidence: 99%
“…Anthropogenic (secondary) salinisation of arid and Mediterranean lands occurs globally and influences the distribution of aquatic assemblages across the landscape (Roberts & Irving-Bell, 1997;Halse et al, 2003;Hart & Lovvorn, 2005;Pinder et al, 2005;Piscart et al, 2005b). General consensus exists that increasing river and wetland salinity has potential to cause local extinctions, alterations in ecosystem function and extensive environmental damage (Halse et al, 2003;Kefford et al, 2003;Jardine et al, 2007). Halse et al (2003) predicted that approximately one-third of aquatic invertebrate diversity in the inland southwest of Western Australia (WA) will disappear with the expansion of secondary salinisation, and Pinder et al (2005) suggested that up to 100 species that are largely restricted to the inland southwest are at risk of extinction.…”
Section: Introductionmentioning
confidence: 99%
“…Currently more than one million hectares are affected and salinisation is expected to expand twoto fourfold by 2050 (George et al, 2006;Jardine et al, 2007). Ephemeral water bodies are characteristic of the Wheatbelt, where they show a range of salinities, especially in areas affected by secondary salinisation, making them ideal to investigate how salinity affects the colonisation and oviposition behaviour of insects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MacGregor and Cary 2002, Jardine et al 2007, Speldewinde et al 2009 • Increase in Ross River Virus carrying mosquitoes in saline biodiversity poor areas, but impact on humans minimal because of low population densities; • Any decrease in native biodiversity or change in ecosystem could potentially pose a disease risk (e.g., Lyme disease or Hanta virus in U.S.); • Depending on land-use changes, increases in airborne dust will increase lung and eye problems. Agriculture…”
Section: Adaptation Strategiesmentioning
confidence: 99%